Equine keratomycoses in California from 1987 to 2010 (47 cases). (4th September 2012) - Reed, Z.; Thomasy, S. M.; Good, K. L.; Maggs, D. J.; Magdesian, K. G.; Pusterla, N.; Hollingsworth, S. R.
Summary Reasons for performing study: Equine keratomycosis in the western USA has received little study, probably owing to its low prevalence. Objectives: To determine clinical features, predominant fungal isolates, treatment modalities and outcomes of horses with keratomycosis in California and compare these with results from different geographic regions. Methods: Records of horses presented to the University of California‐Davis Veterinary Medical Teaching Hospital (UCD‐VMTH) with confirmed keratomycosis between 1987 and 2010 were reviewed for this retrospective study. Information retrieved from the record included background, ophthalmic examination findings, treatment prior to and following presentation, visual outcome, and ocular survival. Results: A total of 48 eyes in 47 horses met the inclusion criteria and comprised 2% of cases presented to the UCD‐VMTH ophthalmology service. Prior to presentation, 20 horses (43%) received at least one topically administered anti‐inflammatory medication. Keratomycosis was confirmed by fungal culture in 38 horses (81%), by histopathology in 2 horses (4%) and by cytology in 7 horses (15%). Forty‐four isolates were identified in the 38 horses cultured; Aspergillus was the most common isolate (64%) and a novel isolate, Papulospora, was identified in 2 horses. Treatment consisted of medication only (73%), medical and surgical treatment (25%), or immediate enucleation (2%). Globe retention was 77% and vision retention was 53%. Corneal perforation was significantly associated with loss of vision (P<0.001). Conclusions: Keratomycosis is relatively uncommon in horses presented for ophthalmic conditions at UCD‐VMTH. Corneal perforation was a negative prognostic indicator for vision in this population of northern Californian horses.